On Dominator Chromatic Number Of Radial Graph Of Some Graphs - R, Kalaivani; D, Vijayalakshmi (Kongunadu Research Journal, 2019)
A dominator coloring is a coloring of the vertices of a graph such that every vertex is either alone in its color class or adjacent to all vertices of at least one other class. In this paper, we obtain the Dominator Chromatic number of the Radial graph for the Central graph of Star graph, Super-radial graph for Middle graph of Cycle and Central graph of Path.